The Effect of Problem Based Learning with Laboratory Activities on Students’ Problem-Solving Skills - Diana, Rhifa; Surahman, Endang; Makiyah, Yanti Sofi (Jurnal Pendidikan MIPA, 2022)
This research is motivated by the low problem-solving skills of students in the kinetic theory of gases and the lack of innovation in the use of models in physics learning. Efforts made by researchers to overcome these problems are by applying a laboratory-based PBL learning model. The purpose of this study was to determine the effect of the laboratory-based PBL learning model on students' problem-solving skills on gas kinetic theory material in class XI IPA SMA Negeri 1 Cilimus. The research method used is a quasi-experimental research design with a pretest-posttest control group design. The results show that after the implementation of the laboratory-based PBL model, it is obtained that is tcount > ttable so that H_0 is rejected, can be concluded that there is an influence of the laboratory-based PBL learning model on problem solving skills in gas kinetic theory material in class XI IPA SMA Negeri 1 Cilimus.Keywords: problem-solving skills, problem based learning, laboratory activities, kinetic gas theory.DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp1017-1029